Enhancing gait training with anti-gravity treadmill ‘Alter-G’ in patients with Parkinson’s disease - Desireè Latella; Antonino Lombardo Facciale; Mirjam Bonanno; Lilla Bonanno; Antonino Leo; Roberta Cellini; Giuseppe Di Lorenzo; Piero Buonasera; Caterina Formica; Giuseppe Paladina; Luca Pergolizzi; Bartolo Fonti; et al. (PLoS ONE, 2026)
Background Freezing of Gait (FoG) is a debilitating motor symptom affecting nearly half of individuals with Parkinson’s disease (PD), increasing fall risk and reducing independence. Despite pharmacological and neuromodulation therapies, residual symptoms often persist, underscoring the need for complementary rehabilitation strategies. Objective To evaluate the effects of body weight–supported treadmill training using differential air pressure on gait and mobility in PD patients. Methods Forty patients with idiopathic PD were randomly assigned to an experimental group (EG, n = 20), who received gait training with a lower-body positive pressure treadmill, or to a control group (CG, n = 20), who underwent conventional physiotherapy. Both groups trained twice weekly for 4 months. Outcomes were assessed at baseline (T0) and post-intervention (T1), and classified as primary (gait speed, step length, balance, postural stability) or secondary (quality of life, fear of falling, anxiety). Results Compared to controls, the EG showed significant improvements in gait speed, step length, balance, and postural stability (all p < 0.01). Secondary outcomes also improved, with reductions in fear of falling (p < 0.01) and better quality of life scores (p < 0.01). Conclusions This pilot trial suggests that body weight–supported treadmill training through differential air pressure may improve gait performance and postural control, while also enhancing quality of life in PD patients with mobility impairments and FoG. These preliminary findings support its potential role as a complementary rehabilitation strategy, warranting confirmation in larger trials.